Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Kreativitas Seni Rupa Siswa Kelas V SDN 166 Laburawung Kecamatan Lalabata Kabupaten Soppeng - Nabila Sabrina; Awaluddin Muin; Firdaus (MACCA : Science-Edu Journal, 2026)
This research is a Classroom Action Research (CAR) that aims to determine the application of the Project Based Learning Model to improve the creativity of fifth grade students at SDN 166 Laburawung, Lalabata District, Soppeng Regency. The subjects of this study were all 15 fifth-grade students and their homeroom teacher. Data collection techniques included documentation, teacher and student observation, and student creativity performance tests. Data analysis techniques in this study included data reduction, data presentation, and conclusion drawing. The results of the study show that the percentage of teacher activity in cycle I reached the category of Fair (C) and in cycle II increased to the category of Good (B). The study shows that student creativity in Fine Arts learning in cycle I was 60% or 9 students obtained an average score of 68.27 with a sufficient (C) qualification and increased in cycle II by 86.67% or 13 students with an average score of 83.33 with a good (B) qualification. It can be concluded that the Project-Based Learning model can improve student creativity in Fine Arts learning.